PELATIHAN PEMANFAATAN PENGEMBANGAN HASIL RISET: MEDIA EDUKASI FRACTION BAKERY UNTUK PEMBELAJARAN MATEMATIKA PADA PENDIDIKAN DASAR - Chrisnawati, Henny Ekana; Usodo, Budi; Nurhasanah, Farida; Kuswardi, Yemi; Sutopo, Sutopo (DEDIKASI: Community Service Reports, 2025)
The aim of this community service activity is to introduce the use of mathematics learning media for the topic of fractions, called Fraction Bakery, which has been developed by the service team in the Contemporary Mathematics Education research group for 2 years, both in tangible and online game forms. The initial development of the Fraction Bakery educational media was based on the complaints and difficulties expressed by students and teachers in learning and teaching fraction concepts. As fractions have various forms and are related to decimal numbers, percentages, and comparisons, selecting suitable learning models and media for elementary school students becomes crucial. Choosing an interactive learning model or media that is enjoyable for students, considering that the target users are students who are still in the concrete operational stage based on Piaget's developmental theory, is important. The development of Fraction Bakery media followed the five-stage R&D ADDIE model. Training programs were conducted using the School-Based and Collaborative Teacher Professional Development (TPD) approach, with the SUN program as a dissemination strategy. The training included mentoring sessions for teachers by media experts from PT Sebangku Jaya Abadi in collaboration with the research team. The training sessions, which took place over 32 hours at SD Negeri 15 Sragen, received highly positive responses from participants. Approximately 86.45% of teachers expressed that the material was suitable for their teaching needs, 87.5% found it easy to implement, 90.6% acknowledged the practical benefits of the training, and 89.58% found the material engaging.